AN IMPROVEMENT OF POWER POINT TRACKING WEAR METHOD DC-DC CONVERTER METHOD PLTU BAYU BASED ON FUZZY LOGIC - Ari Pahala Situmorang; Solly Aryza; Hamdani (Sean Institute, 2022)
In increasing the electrical power capacity of the Wind Power Plant (PLTB) there are several ways, among others, by increasing the number of generators, but the drawback is that the cost is too expensive because they have to build new plants. Another way is to increase the output power efficiency of existing wind power plants. One way is to use Maximum Power Point Tracking (MPPT) technology which functions to increase the output power of the power plant when there is a change in wind speed. In this paper, this technology is in charge of regulating the generator output voltage through a DC-DC converter type Cuk Converter, where the switching technique uses PWM (Pulse Width Modulation) by adjusting the amount of duty cycle. Changes in the value of the duty cycle depending on the size of the wind speed, so that to adjust the value of the duty cycle and speed up the switching response of the PWM control, a modern algorithm called the Fuzzy Logic Controller (FLC) is used. The results showed that FLC-based MPPT technology could increase the percentage of PLTB output power efficiency from 45.5% to 87%.